Nutrient removal and release in wetland buffer zone and perception of the local community opportunities and threats to nature-based wastewater treatment in Lake Danao, Ormoc City, Philippines - Toralde, Cherryhel B.
Lakes are essential freshwater ecosystems in the Philippines. In Ormoc City, Leyte, Lake Danao in Lake Danao Natural Park (LDNP) is utilized in various ways such as domestic water, irrigation, eco-tourism, and source of freshwater food for the locals. However, Lake Danao is vulnerable to water quality degradation and pollution caused by the discharge of unfiltered wastewater from residential, agricultural, and socio-economic activities on the surrounding land. This study explores the opportunities and threats to sustainable nature-based wastewater treatment in Lake Danao, by assessing the nutrient removal capacity of the wetland buffer zone (WBZ) and evaluating the important community attributes in the protected area. Nitrate removal ranges from 0%-100% and phosphate removal ranges from 43.64% - 75.47%. Phosphate release was also observed mainly in site 2, which is near the residential areas, and may be attributed to low vegetation cover in the area, that through normalized difference vegetation index, site 2 was shown to have sparse vegetation. In addition, there was a positive outcome on the knowledge, perceptions, and attitude of the local community towards the WBZ, as well as common practices related to lake water management. The results will serve as a preliminary data for recommending nature-based and behavioral approaches in maintaining and managing the quality of water resources in Lake Danao.